Influência do operador e agente cimentante na resistência de união de pinos de fibra de vidro à dentina radicular - (:unkn) unknown (UNIVERSIDADE ESTADUAL DE PONTA GROSSA, 2010)
The aim of this study was to evaluate the influence of the operator skill and resin cement system on the bond strength (BS) of glass fiber post to radicular dentin in different root thirds. Forty-eight extracted human upper central incisors were sectioned transversally immediately below the cement-enamel junction and the roots were treated endodontically. After one week, standardized post space cavities were prepared, and the roots randomly divided into two groups (n=24), according to the operator skill: professional (CD) vs academic (AC). The roots were then subdivided into three subgroups (n=8) according to the cementation system: CD1 and AC1 (Adper Scotchbond Multi-Purpose [SBMP] + RelyX ARC [ARC]), CD2 and AC2 (Adper Single Bond 2 [SB] + ARC) and CD3 and AC3 (RelyX U100 [U100]). The glass fiber post (Tenax Fiber Trans Esthetic Post System) were cemented following the manufacturer’s instructions of each cementation system. After water storage at 37o C for one week, each root was sectioned transversely into six 1-mm thick discs and the coronal (TC), middle (TM) and apical (TA) thirds of the root canal identified. A push-out test was carried out at a crosshead speed of 0,5 mm/min. The data were statistically analyzed by ANOVA and post-hoc Tukey's tests (p=0.05). The mean bond strengths (BS) values (MPa) and standard deviations (SD) of each subgroup were: CD1: 12.83±7.26; CD2: 11.46±4.22; CD3: 14.27±6.59; AC1: 9.70±4.37; AC2: 8.02±5.25 and AC3: 13.40±4.93. The BS of the CD and AC groups were 12.85±6.18 and 10.37±5.30, respectively. In regard to the root thirds, the means and SD were: TC: 14.46±5.55; TM: 10.04±5.07 and TA: 10.35±6.01. The mean and SD for the cementation systems were: SBMP + ARC: 11.27±6.13; SB + ARC: 9.74±5.03 and U100: 13.83±5.77. The highest BS means were obtained for CD group (p=0.004); no significant differences were detected among the three cementation systems for CD group (p=0.294); U100 cement reached statistically higher BS than the other cementation systems for AC group (p=0.001). The resin cement U100 was statistically higher than the other materials (p=0.0010) regardless the operator skill. The BS in the cervical third was statistically higher than in the TM and TA (p<0.0001). It can be concluded that the bond strength to the root canal is significantly affected by the operator skill, cementation system and root region.
Influence of the operator skill and luting agent on the bond strength of glass fiber post to radicular dentin.
Keywords: cimentos resinosos; operador; pinos de fibra; Push-out; resistência de união; resin cements; operator; fiber posts; push-out; bond streng; CNPQ::CIENCIAS DA SAUDE::ODONTOLOGIA::CLINICA ODONTOLOGICA